Mindfulness-Based Interventions for In-Patients With Schizophrenia Spectrum Disorders—A Qualitative Approach - Böge, Kerem; Karadza, Almira; Fuchs, Lukas M.; Ehlen, Felicitas; Ta, Thi Minh Tam; Thomas, Neil; Bajbouj, Malek; Hahn, Eric (Frontiers in Psychiatry, 2020)
In recent years, mindfulness-based interventions (MBI) have gained clinical relevance in the treatment of patients with schizophrenia spectrum disorders (SSDs). High symptom burden, long durations of hospitalization and high rehospitalization rates demonstrate the severity and cost-intensity of these disorders. MBIs have shown promising treatment outcomes in a small number of trials, primarily taking place in English-speaking countries. The current study aims to explore mechanisms and processes as well as adverse effects of MBIs on in-patients with SSDs in a German university hospital setting. A qualitative design based on inductive thematic analysis accompanied by quantitative assessments was chosen. A semi-structured interview guide was developed by psychiatrists and psychologists to assess patient experiences, perceptions, thoughts, and feelings during and after taking part in a MBI. Twenty-seven interviews were conducted between September 2017 and October 2018 with in-patients who are diagnosed with schizophrenia or schizoaffective disorder. Rater-based questionnaires, such as the Positive and Negative Syndrome Scale (PANSS), Montgomery Asberg Depression Rating Scale (MADRS), and Psychotic Symptom Rating Scales-Auditory Hallucination (PSYRATS-AH) were administered at baseline to collect clinical outcomes. Qualitative analysis revealed two domains: content and function. In the first domain related to content with the core elements “detachment and rumination”, “presence and getting lost”, “non-judgment and judgment”, and effects with “emotions”, “cognition”, and “symptom changes”. A second domain related to function was extracted, including the relevance of perception of context and transfer to everyday life. Overall, improvements concerning cognition, distress, and psychopathology were detected, while no adverse effects, such as increased psychotic symptoms, were revealed. As the first study of its kind, mechanisms, processes, and the safety of MBIs were explored and confirmed in a sample of German in-patients with SSDs. The results of this qualitative study are in line with recent findings on MBIs amongst patients with psychotic disorders from other countries. Results lay the ground for future research to focus on the systematic study of MBIs in large samples, its treatment processes, outcomes, and effectiveness for in-patients with SSDs.